Pembelajaran Fiqih Berbasis Masalah melalui Kegiatan Musyawarah di Pondok Pesantren Al-Anwar Sarang Rembang - Rohman, Fathur (Universitas Islam Negeri Raden Intan Lampung, 2017)
This article provides a description of the implementation of problem-based learning of fiqih with musyawarah activities at Pondok Pesantren Al-Anwar Sarang Rembang Central Java. The problem of this article focuses on two problems, how the implementation of problem-based learning of fiqih by musyawarah at Pondok Pesantren Al-Anwar and the advantages and disadvantages of problem based-learning of fiqh with musyawarah activities. This paper is the result of qualitative research using case study method. Data collection used participant observation, interview, and documentation techniques. To determine the sample of data source as informant, this research uses purposive sampling and snowball sampling technique. The data analysis technique used is descriptive qualitative analysis with phenomenology approach. The Analysis begins since the researcher goes to the place and it is done interactively and continuously until being completed. It can be concluded that the activities of musyawarah is a form of problem-based learning of fiqih in the style of pesantren. In terms of principles, characteristics, as well as learning stages in musyawarah activities have been in accordance with the concept of problem-based learning.